2013
DOI: 10.1371/journal.pone.0080580
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pancreatic Cancer Cell Lines Derived from Genetically Engineered Mouse Models of Spontaneous Pancreatic Adenocarcinoma: Applications in Diagnosis and Therapy

Abstract: Pancreatic cancer (PC) remains one of the most lethal human malignancies with poor prognosis. Despite all advances in preclinical research, there have not been significant translation of novel therapies into the clinics. The development of genetically engineered mouse (GEM) models that produce spontaneous pancreatic adenocarcinoma (PDAC) have increased our understanding of the pathogenesis of the disease. Although these PDAC mouse models are ideal for studying potential therapies and specific genetic mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 29 publications
7
117
0
Order By: Relevance
“…Binding of p65 also corresponded to enhanced occupancy of phosphorylated RNA polymerase II (pPol II, which is phosphorylated on serine 2) ( Figure 4F), suggesting that the binding of p65 to exon 2 of Gdf-15 promotes active transcription. To further substantiate these findings, we constructed a luciferase reporter plasmid containing the NF-κB-binding element from exon 2 of Gdf- 15. Results showed that GDF-15 reporter activity was enhanced in p65 +/+ Ras MEFs and in cells stimulated by TNF (Figure 4, G and H).…”
Section: Ras Mefsmentioning
confidence: 79%
See 1 more Smart Citation
“…Binding of p65 also corresponded to enhanced occupancy of phosphorylated RNA polymerase II (pPol II, which is phosphorylated on serine 2) ( Figure 4F), suggesting that the binding of p65 to exon 2 of Gdf-15 promotes active transcription. To further substantiate these findings, we constructed a luciferase reporter plasmid containing the NF-κB-binding element from exon 2 of Gdf- 15. Results showed that GDF-15 reporter activity was enhanced in p65 +/+ Ras MEFs and in cells stimulated by TNF (Figure 4, G and H).…”
Section: Ras Mefsmentioning
confidence: 79%
“…Therefore, we expanded our analysis generating additional Gdf- 15- (15,16) that also stably expressed a luciferase reporter gene that was used for bioluminescence imaging (17) (Figure 3A). KPC control or KPC Gdf-15-knockdown clones were then orthotopically injected into the tail of the pancreas of C57BL/6 albino mice, and tumor development was visualized.…”
Section: Ras Mefsmentioning
confidence: 99%
“…PDAC cells were maintained in DMEM with 10% (vol/vol) FBS and 1% penicillin/streptomycin in a 5% (vol/vol) CO 2 and 95% (vol/vol) air incubator. All cell lines (P8, A6L, A32, P198, E3, P215, P10, JD13D) were generated from PDAC tumors as previously described (46)(47)(48) and kindly provided by Anirban Maitra (MD Anderson Cancer Center, Houston). To determine glutamine dependence, cells were grown with or without glutamine in DMEM with 10% (vol/vol) dialyzed FBS and 1% penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…This stringent PDAC tumor model mimics human PDAC for oncogene expression, growth characteristics, metastasis, histological features, and development of a dysplastic stroma (28,29). Figure 1B summarizes the details of the tumor growth characteristics and metastasis as seen during animal autopsy and IVIS imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Pdx1-Cre mouse) (27)(28)(29). In addition, silicasomes also provide major toxicity reduction in the gastrointestinal tract, liver, and bone marrow compared with the liposomal equivalent (27).…”
Section: Introductionmentioning
confidence: 99%